The Impact of The Tahfdz Quarantine Program on Improving Students’ Memorization at Miftahul Huda Tahfidz Community Boyolali - Hannin, Shafa Fadilah; Salim, Hakimuddin (Journal of Educational Sciences, 2025)
The Qur'an memorization quarantine program has become a strategy implemented in various Islamic boarding schools to improve the quality and quantity of students' memorization. This study was conducted to analyze the effectiveness of the memorization quarantine program at Pondok Pesantren Miftahul Huda Tahfidz Community (MHTC) Boyolali in enhancing students' memorization, as well as to identify challenges and strategies that can be applied to optimize memorization outcomes. Based on Bandura's Social Learning Theory (1977) and Sweller's Cognitive Load Theory (1988), this research examines how the learning environment and cognitive load affect the effectiveness of the intensive memorization program. This study employs a qualitative approach with in-depth interviews conducted with students and female teachers at Pondok Pesantren Miftahul Huda. The findings show that the program significantly increased students' memorization quantity in a short period, as also found in previous studies.